Association of coping strategies with symptoms of burnout in young football players in a career transition phase: Are professionalization and occurrence of injuries mediating factors? - Alves da Silva, A. A.; Morais Freire, G. L.; Vila Nova de Moraes, J. F.; de Souza Fortes, L.; da Silva Carvalho, R. G.; Andrade do Nascimento Junior, J. R. (The Sport Psychologist, 2021)
This study investigated the association of coping strategies burnout symptoms in 228 Under-20 Brazilian soccer players in a career transition phase and compared these variables with the occurrence of injuries and professionalization. The instruments used in the study were the Athlete Burnout Questionnaire and the Athletic Coping Strategies Inventory-28. Data analysis was conducted through generalized estimation equations, Pearson correlation, and multiple linear regression (p < .05). The results showed that coping was associated with physical and emotional exhaustion in both professional and nonprofessional players, and with a reduced sense of accomplishment only in young nonprofessional athletes who were in the career transition phase. It is concluded that young elite athletes who are in the transition phase of their career but have not signed a professional contract, use limited coping strategies and seem more exposed to stress (compared with those who have signed a contract), and are consequently more vulnerable to burnout symptoms.